The Ecology of Collective Behavior - Gordon, Deborah M. (Princeton University Press, 2023)
A groundbreaking new perspective on collective behavior across biological systemsCollective behavior is everywhere in nature, from gene transcription and cancer cells to ant colonies and human societies. It operates without central control, using local interactions among participants to allow groups to adjust to changing conditions. The Ecology of Collective Behavior brings together ideas from evolutionary biology, network science, and dynamical systems to present an ecological approach to understanding how the interactions of individuals generate collective outcomes.Deborah Gordon argues that the starting point for explaining how collective behavior works in any natural system is to consider how it changes in relation to the changing world around it. She shows how feedback use-the means by which networks of interactions operate-and the organization of interaction networks evolve to reflect the stability and demands of the environment. Ant colonies function collectively, and the enormous diversity of species in different habitats provides opportunities to look for general ecological patterns. Through an in-depth comparison of ant species, Gordon identifies broad trends in how the diversity of collective behavior in many other collective systems reflects the dynamics of the environment.Shedding light on how individual actions give rise to group behavior, The Ecology of Collective Behavior explains the evolution of collective behavior through innovation in participant interactions, offering new insights into how collective responses function in changing conditions